Low Dielectric Constant and Anisotropic Mechanical Properties of Dispenser‐Printed Polyetherimide Films Using Two‐Step Thermal Treatment. Issue 10 (20th July 2022) - Kim, Junyoung; Hwang, Uiseok; Chung, June‐young; Kim, Na‐Yeon; Nam, Jeonghyeon; Jung, Jinho; Sun, Hanna; Seol, Mina; Park, In‐Kyung; Suhr, Jonghwan; Nam, Jae‐Do
Abstract: Although polyetherimide (PEI) has attracted attention owing to its good dielectric properties, superior mechanical properties, and thermal/chemical stabilities, there is still a lack of methodology to fabricate PEI films in desired shapes directly on devices. In this study, a dispenser printing method to fabricate sophisticated 2D PEI structures is introduced. As dispenser printing is a solution‐based process, PEI ink is prepared by dissolving PEI in N ‐methyl pyrrolidone (NMP). The printing conditions are controlled by optimizing the pneumatic pressure and viscosity of the inks with various ratios of PEI and NMP, followed by a two‐step heat treatment to develop fine PEI films. The dielectric constant of the PEI film increases from 2.28 to 2.61 with the corresponding secondary heating time of 1–5 h, which is much lower than the theoretical value owing to the free volume and loosely entangled polymer chains generated from the shear forces in printing and solvent evaporation. Furthermore, the film exhibits anisotropic mechanical properties in different printing directions, stemming from the alignment effect of the polymer molecules. It is believed that the developed PEI films and the facile methodology can be diversely tuned to provide new insights into material utilization, further extending the application fields. Abstract : Dispenser printing for polyetherimide film fabrication is reported to widen materials system design and flexibilities, of which the printing conditions are optimized based on the viscosity of ink, pneumatic pressure, and heat treatment. Combined with the relatively low dielectric constant and unique anisotropic mechanical properties, the results suggest a new paradigm in processing for advanced engineering plastics.